BENEFICIAL MICROORGANISMS IN THE ROOT REGION SOILS OF COCONUT PALM UNDER DIFFERENT CROPPING SYSTEMS A REVIEW - B. M. Bopaiah (International Coconut Community, 1994)
The coconut palm is amenable to intensive crop combinations at most periods of its life and great possibilities exist for increasing the agricultural production through intensive cropping in coconut areas. Coconut palms are grown under diverse soil conditions ranging from littoral sands to clayey soils (Menon and Pandalai, 1960). In pure stand of coconuts at normal planting (7.5 x 7.5 m) density and management conditions, about 75% of the area is not being effectively utilised to the fullest extent by coconut roots (Kushwah et al. 1973). The intensive cropping system involving coconuts are essentially crop combinations which envisage the cultivation of other compatible crops in the interspaces between the palms. Depending upon the duration of additional crops, so grown, the system shall be considered as inter, mixed, multi‑storeyed or multispecies cropping. The crops chosen vary from tract to tract (Nelliat and Shama Bhat, 1979).